2004
DOI: 10.1007/s00439-004-1114-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the MID1 protein function is fine-tuned by a complex pattern of alternative splicing

Abstract: Clinical features of Opitz BBB/G syndrome are confined to defects of the developing ventral midline, whereas the causative gene, MID1, is ubiquitously expressed. Therefore, a non-redundant physiological function of the MID1 product appears to be developmentally restricted. Here, we report the identification of several alternative MID1 exons in human, mouse and fugu. We show that splice variants of the MID1 gene that are comparable in terms of function occur in the three organisms, suggesting an important role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…Furthermore, recombination in F1 hybrids between M. m. castaneus CAST and other subspecies would create Mid1 transcripts that contain a subset of highly diverged M. m. castaneus CAST exons. Mid1 is known to have a large number of tissue-specific splice variants (Winter et al 2004). Combining exons from different subspecies may result in transcripts with altered tissue expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recombination in F1 hybrids between M. m. castaneus CAST and other subspecies would create Mid1 transcripts that contain a subset of highly diverged M. m. castaneus CAST exons. Mid1 is known to have a large number of tissue-specific splice variants (Winter et al 2004). Combining exons from different subspecies may result in transcripts with altered tissue expression.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative splicing is well established to have roles in both regulation of expression and in the generation of protein function diversity, as illustrated by many detailed studies of genes, such as CD44 (36), NOVA (37), ABCC4 (38), MID1 (39) and hUPF2 (40). Although exact estimates vary, it is also clear that that 10–30% of alternative splicing events are tissue specific (41), suggesting function.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the post-transcriptional regulation of the Mid1 mRNA has shown that alternative use of different transcription start sites, alternative splicing, and the existence of different polyadenylation signal results in a wide variety of Mid1 isoforms (Landry and Mager, 2002; Winter et al, 2004). Less is known, however, about the transcriptional mechanisms that regulate Mid1 expression.…”
Section: Discussionmentioning
confidence: 99%